2018
DOI: 10.1007/s11136-018-2004-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of three exercise approaches on health-related quality of life, and factors associated with its improvement in chronic whiplash-associated disorders: analysis of a randomized controlled trial

Abstract: ClinicalTrials.gov, No. NCT01528579.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 47 publications
2
11
0
Order By: Relevance
“…It could be the lack of neck-specific exercise or the lack of guidance. Nevertheless, this is consistent with other outcomes from the main study, such as general health-related quality of life 38 , neck disability 39 , self-reported work ability 40 , pain catastrophising, anxiety and kinesiophobia 41 , where there was also a trend for the PPA group towards deterioration over time. However, as seen in Fig.…”
Section: Discussionsupporting
confidence: 89%
“…It could be the lack of neck-specific exercise or the lack of guidance. Nevertheless, this is consistent with other outcomes from the main study, such as general health-related quality of life 38 , neck disability 39 , self-reported work ability 40 , pain catastrophising, anxiety and kinesiophobia 41 , where there was also a trend for the PPA group towards deterioration over time. However, as seen in Fig.…”
Section: Discussionsupporting
confidence: 89%
“…It is important to also recognize these findings support previous preliminary cross-sectional work involving patients with varying levels of chronic WAD-related disability and healthy controls across two cultures (United States 1 and Sweden 7 ); where different insurance schemes and medical/rehabilitative options may influence recovery. While larger proportions of MFI in the multifidus muscles have been attributed to severe WAD, further prospective investigations, with larger sample sizes, are required to identify an element of pre-existing organic origins [19][20][21] , specific injury mechanisms underlying MFI 22,23 , biomechanical consequences [24][25][26][27][28] and their relationships to the further development of MFI with a long-term goal of informing clinical trials; exercise in particular 29 .…”
Section: Discussionmentioning
confidence: 99%
“…All continuous variables (i.e. variables 1 to above) were assessed at baseline, 3, 6, and 12 months follow-up, with the exception of the Hospital Anxiety and Depression Scale anxiety sub-score (HAD_A), Hospital Anxiety and Depression Scale depression sub-score (HAD-D), and Tampa Scale for Kinesiophobia (TSK) which were not measured at 3 months [40]. The maximum proportion of missing data was at 39.4% for the WAI data at 12 months follow-up.…”
Section: Approach To Sample Selectionmentioning
confidence: 99%